Development of the Parental Modelling of Eating Behaviours Scale (PARM): links with food intake among children and their mothers. Issue 4 (20th August 2012) - Palfreyman, Zoe; Haycraft, Emma; Meyer, Caroline
Abstract This study aimed to develop a self‐report questionnaire to explore parental modelling of eating behaviours and then to use the newly developed measure to investigate associations between parental modelling with healthy and unhealthy food intake in both mothers and their children. Mothers (n = 484) with a child aged between 18 months and 8 years completed the Parental Modelling of Eating Behaviours Scale (PARM), a new, self‐report measure of modelling, as well as a food frequency questionnaire. Principal components analysis of the PARM identified 15 items grouped into three subscales: verbal modelling (modelling through verbal communication); unintentional modelling (UM) (children adopting eating behaviours that parents had not actively modelled); and behavioural consequences (children's eating behaviours directly associated with parental modelling). The PARM subscales were found to be differentially related to food intake. Maternally perceived consequences of behavioural modelling were related to increased fruit and vegetable intake in both mothers and children. UM was related to higher levels of savoury snack intake in both mothers and their children. This study has highlighted three distinct aspects of parental modelling of eating behaviours. The findings suggest that mothers may intentionally model healthy food intake while unintentionally acting as role models for their children's less healthy, snack food intake.